ASME 2015 13th International Conference on Nanochannels, Microchannels, and Minichannels 2015
DOI: 10.1115/icnmm2015-48428
|View full text |Cite
|
Sign up to set email alerts
|

Microchannel Flow Enhancement by Microplasma Actuation

Abstract: Microscale plasma actuators operate at lower voltages than their macroscale counterparts and allow easy integration into microsystems. Field-emission driven microplasma actuators can be applied for gas flow enhancement in microchannels for pumping and microcombustion applications. The present work studies the feasibility of microplasma actuation as a pump for gaseous microchannel flow. We use 2D Particle-In-Cell / Monte Carlo Collisions (PIC/MCC) method to calculate the volumetric force generated by field-emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…For pure H 2 , the peak of period-averaged Joule heating is 19×10 9 W/m 3 . This is similar to the prediction of 20×10 9 W/m 3 reported in similar studies for an FE-DBD in atmospheric pressure N 2 [8,46]…”
Section: Source Terms For the Continuum Modelsupporting
confidence: 90%
See 2 more Smart Citations
“…For pure H 2 , the peak of period-averaged Joule heating is 19×10 9 W/m 3 . This is similar to the prediction of 20×10 9 W/m 3 reported in similar studies for an FE-DBD in atmospheric pressure N 2 [8,46]…”
Section: Source Terms For the Continuum Modelsupporting
confidence: 90%
“…The force pushes gas around the corner of the exposed electrode with magnitude greatest at the corner: 40×10 6 N/m 3 in pure O 2 and 10.5×10 6 N/m 3 in pure H 2 . Its distribution and magnitude in H 2 match those predicted for the same electrodes in nitrogen [8,46]. This previous study also found a force magnitude of 10×10 6 N/m 3 at the corner of the exposed electrode, matching our magnitude of 10.5× 10 6 N/m 3 .…”
Section: Source Terms For the Continuum Modelsupporting
confidence: 89%
See 1 more Smart Citation
“…An electric potential of −300 V is applied at a frequency of 10 MHz to the exposed electrode, and the buried electrode remains grounded. Such a design was found to maximize flow actuation in previous studies [13,29]. The oscillating electric field stimulates FE of electrons from the corner of the exposed electrode, ionizing the gas and dissociating molecules through electron impact.…”
Section: Fe-dbd Arraysmentioning
confidence: 99%
“…The device is driven by an AC voltage of −325 V at a frequency of 10 MHz and operates at atmos pheric pressure. Theoretical and computational studies of flow actuation by 4 such actuators in a microchannel of height 500 µm exhibit an average velocity of 3.8 m s −1 and temperature of 710 K at the exit [20][21][22]. The field emission from such a device can be enhanced by coating the electrode surface with carbon nanopetals [23,24] which creates irregularities to increase the surface roughness.…”
Section: Introductionmentioning
confidence: 99%